Pleiotropic effects of recombinant protease inhibitors in plants - Mangena, Phetole (Frontiers in Plant Science, 2022)
Recombinant gene encoded protease inhibitors have been identified as some of the most effective antidigestive molecules to guard against proteolysis of essential proteins and plant attacking proteases from herbivorous pests and pathogenic microorganisms. Protease inhibitors (PIs) can be over expressed in transgenic plants to complement internal host defense systems, Bt toxins in genetically modified pest resistance and abiotic stress tolerance achieved through cystatins expression. Although the understanding of the role of proteolytic enzymes and their inhibitors encoded by both endogenous and transgenes expressed in crop plants has significantly advanced, their implication in biological systems still requires further elucidations. This paper, therefore, succinctly reviewed most recently published literature on recombinant proteases inhibitors (RPIs), focusing mainly on their unintended consequences in plants, other living organisms, and the environment. The review discusses major negative and unintended effects of RPIs involving the inhibitors’ non-specificity on protease enzymes, non-target organisms and ubiquitous versatility in their mechanism of inhibition. The paper also discusses some direct and indirect effects of RPIs such as degradation by distinct classes of proteases, reduced functionality due to plant exposure to severe environmental stress and any other potential negative influences exerted on both the host plant as well as the environment. These pleiotropic effects must be decisively monitored to eliminate and prevent any potential adverse effects that transgenic plants carrying recombinant inhibitor genes may have on non-target organisms and biodiversity.